Modulation of human thrombopoietin receptor conformations uncouples JAK2 V617F-driven from cytokine-induced activation - Papadopoulos, N; Pristavec, A; Nédélec, A; Levy, G; Staerk, J; Constantinescu, SN (American Society of Hematology, 2023)
The Thrombopoietin Receptor (TpoR) is a central player in Myeloproliferative Neoplasms (MPNs). Mutations in JAK2, calreticulin or in TpoR itself drive constitutive activation of TpoR and uncontrolled proliferation and differentiation of hematopoietic stem cells and progenitors. The JAK2 V617F mutation is responsible for the majority of MPNs and all driver mutants induce pathologic TpoR activation. Existing therapeutic strategies have focused on JAK2 kinase inhibitors that are unable to differentiate between the mutated MPN clone and healthy cells. Surprisingly, targeting of TpoR itself has remained poorly explored despite its central role in the pathology. Here, we performed a comprehensive characterization of human TpoR activation in physiological and pathological conditions focusing on the JAK2 V617F mutant. Using a system of controlled dimerization of transmembrane and cytosolic domains of TpoR, we discovered that the human TpoR (hTpoR) adopts different dimeric conformations upon Tpo-induced versus JAK2 V617F-mediated activation. We identified the amino acids and the specific dimeric conformation of hTpoR responsible for activation in complex with JAK2 V617F and confirmed our findings in the full-length receptor context in hematopoietic cell lines and primary bone marrow cells. Remarkably, we find that modulation of hTpoR conformations by point mutations allows specific inhibition of the JAK2 V617F-driven activation without affecting Tpo-induced signaling. Our results demonstrate that modulation of hTpoR conformation is a viable therapeutic strategy for JAK2 V617F positive MPNs and set the path for novel drug development by identifying precise residues of hTpoR involved in JAK2 V617F specific activation.